ANALISIS PERFORMA EKONOMI PERIKANAN CAKALANG SKALA SEDANG DI ZEE SAMUDERA HINDIA - Andi Irwan Nur; Mennofatria Boer; Dietriech G. Bengen; Awal Subandar (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2014)
Research is aimed at analyzing comprehensively economic performance of middle scale skipjack fisheries in EEZ Indian Ocean. Economic performance is assessed through sensitivity analysis using multidimensional scaling approach with Rapfish ordination techniques of 10 attributes. Scoring criteria for each attribute have been modified according to Indonesia’s fishery contexts. Analysis result shows that economic performance of the fishery is in general still unsatisfactory. Other incomes sources is the worst attribute with sensitivity 5.36 followed by marketable right, limited entry, and ownership with sensitivities 4.92, 4.28, and 4.18 respectively. Sensitivities of other economic attributes show enough to good performances with sensitivities ranging from 3.89 to 1.08. Such results indicating the urgency for rapid responds to manage the worst performance attributes.